Multiple Hereditary Exostoses: Report of an EXT2 Gene Mutation in a Colombian Family - Camacho-Cruz, Jhon; Gutierrez, Luz Dary; Rubio, Cladelis; Suárez, Alfonso; Amaya, Angie (Journal of Pediatric Genetics, 2018)
Multiple hereditary exostoses (MHE) is a rare disease with autosomal dominant inheritance, caused by heterozygous germline mutations in the EXT1 or EXT2 genes. This disorder is characterized by the growth of prominences surrounded by cartilage in the growth plates and the long bones. Here, we report a family affected by MHE. In this family, a pathogenic variant c.544C > T (p. Arg182Ter) was identified in the EXT2 gene. This variant has been previously described in the literature, and here we are reporting the relationship with clinical findings. MHE is suspected according to the clinical manifestations; molecular research should be performed to establish the most frequent mutations. A support, diagnosis, and follow-up group should be created, and genetic counseling should be available for patients and families.
Keywords: hereditary multiple exostoses; EXT1; EXT2; osteochondroma; children